Analyzing Mathematical Creative Thinking Processes in Higher Education: A Learning Style Perspective in Graph Problem Solving - Noviana Dini Rahmawati; Budi Waluya; Mulyono; Iqbal Kharisudin (Hipotenusa: Journal of Mathematical Society, 2025)
This study aims to determine the process of mathematical creative thinking in solving graph problems based on students' learning styles. This research method เว็บสล็อต uses descriptive qualitative. This study was conducted on 5th semester students of the Mathematics Education Study Program, Universitas PGRI Semarang in the 2024/2025 Academic Year. Subjects were taken by purposive sampling. The research instruments were in the form of mathematical creative thinking tests, learning style questionnaires and interview guidelines. R4shub Data analysis techniques included validity, reliability, discriminatory power and difficulty level tests. Furthermore, data validity tests were carried out using the technical triangulation method and qualitative data analysis using an interactive analysis model. The results of the study showed that the mathematical creative thinking process of the average of the four students' learning styles at the preparation stage did not meet the indicators of flexibility and originality. The incubation and illumination stages still need assistance to bring up the originality indicators. เว็บสล็อต While the verification stage has met the four indicators of mathematical creative thinking ability completely. Thus, the findings of this study can be used as a consideration for lecturers in understanding the differences in students' learning styles. Lecturers can provide appropriate scaffolding to make it easier for students to solve graph problems.